DEVELOPMENT OF ROUGH MUTANT E. COLI VACCINE AGAINST COLIFORM MASTITIS - R. Selvaraj; K. Shoba; N. Daniel Joy Chandran; R. Sridhar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Mastitis caused by Gram-negative lactose fermenters which includes Escherichia coli, Klebsiella and Enterobacter species (aerogenes and cloacae) is called as coliform mastitis (Sharma et al., 2012). The incidence of coli form mastitis peaks at post-parturition period soon after the cows enter the lactation cycle (Hogan and Smith, 2003). Since sanitizing by teat dipping, dry cow therapy and treatment have failed to control coliform infections; immunization of dairy cows against coliform mastitis may be a highly valuable procedure to bring these infections under control (Bushnell, 1984). The present study has been undertaken to develop vaccine against coliform mastitis by using local rough E. coli isolate.